Self-assembly of myristic acid in the presence of choline hydroxide: Effect of molar ratio and temperature - Arnould, Audrey (2015)
Salt-free catanionic systems based on fatty acids and cationic surfactants are known to exhibit a broad polymorphism by simply tuning the molar ratio between the two components. In the case of fatty acid combined with organic amino counter-ions, very few data are available on the phase behavior obtained as a function of the molar ratio between the counter-ion and the fatty acid. In this study, we investigated the choline hydroxide/myristic acid system as a function of the molar ratio, R= n choline hydroxide/n myristic acid, and the temperature. At molecular scale, the ionization state of myristic acid was determined as a function of R by coupling pH, conductivity and infra-red spectroscopy measurements. At microscopic scale, the self-assemblies were characterized by small angle neutron scattering and microscopy experiments.For R<1, we showed that the two forms of myristic acid molecules (ionized and protonated)coexisted leading to the formation of facetted objects (vesicles coexisting with discs) and lamellar phases, depending on R. The thermal behavior of the bilayers inside the selfassembly was investigated by differential scanning calorimetry, wide angle X-ray scattering and nuclear magnetic resonance. We showed that the melting process between the gel state and the fluid state of the bilayers induced a structural change from facetted objects and lamellar phases to spherical vesicles. For R>1, all the myristic acid molecules were under their ionized form and only spherical micelles were present in solution. As in the case of catanionic systems, our study highlights that both R and temperature are two key parameters to finely control the self-assembly structure formed by myristic acid in the presence of choline hydroxide.